Model of Self-Identification of Youth in the Global Communication Environment - Bakulov, Viktor D.; Silenko, Svetlana V.; Polomoshnov, Lev A.; Anisimova, Natalya N. (International Journal of Criminology and Sociology, 2022)
Identity is the result of an identification process. The essence of the identification process is expressed in the acceptance of a certain social role by an individual in the process of entering a social group. The psychological meaning of the phenomenon of “identity” reflects the inner identity and integrity of an individual. This phenomenon can affect both an individual and a group. The novelty of the research is determined by the fact that important factors in the process of identity development are specific events in the past and present, periods of crisis and changes in the history of society. It is shown that the main psychological mechanism for the development of identity is identification associated with the interaction between an individual and a social group. The development of personality identity includes a number of types of identity and continues during ontogenesis, is a dynamic and uneven process. The authors show that the concept of national identity within the framework of various fields of psychological science can relate to a group and a person. The practical significance of the study is determined by the fact that in the study the authors understand national identity as the cognitive and emotional awareness of a person of his own belonging to a particular nation, which has its own characteristics. Student (late adolescence) age is decisive in the formation of a person’s identity and sensitive for the development of his national identity. The psychological mechanism for the development of a person’s national identity at this age is national identification. An insufficient study of the development of the national identity of student youth has been established.